2016
DOI: 10.1038/leu.2016.179
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of ABCB1 overexpression in predicting outcome of CML patients undergoing first-line imatinib treatment

Abstract: Tyrosine kinase inhibitor (TKI) therapy results in excellent responses in the majority of patients with chronic myeloid leukaemia. First-line imatinib treatment, with selective switching to nilotinib when patients fail to meet specific molecular targets or for imatinib intolerance, results in excellent overall molecular responses and survival. However, this strategy is less effective in cases of primary imatinib resistance; moreover, 25% of patients develop secondary resistance such that 20-35% of patients ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 52 publications
(36 reference statements)
6
48
0
Order By: Relevance
“…Tyrosine kinase inhibitors (TKIs) and chemotherapy have proven to be highly effective in CML treatment [2]. However, drug transporters, particularly ABCB1 (also known as MDR1, P-glycoprotein, P-gp), play a critical role in drug export and predicate the potential therapeutic responses of CML patients [3][4][5]. Hence, numerous strategies to overcome MDR1-mediated resistance have been explored [6,7].…”
mentioning
confidence: 99%
“…Tyrosine kinase inhibitors (TKIs) and chemotherapy have proven to be highly effective in CML treatment [2]. However, drug transporters, particularly ABCB1 (also known as MDR1, P-glycoprotein, P-gp), play a critical role in drug export and predicate the potential therapeutic responses of CML patients [3][4][5]. Hence, numerous strategies to overcome MDR1-mediated resistance have been explored [6,7].…”
mentioning
confidence: 99%
“…S2, S5), indicating that our models were comparable to others developed in the literature. (28)(29)(30)(31)(32) Ingenuity Pathway Analysis (IPA) performed on the differential expression data for the 370 common genes ( Figure 2C) identified oxidative stress-related and inflammatory processes as altered, e.g. NFkB signaling, as well as decreased signaling by PTEN (a tumor suppressor pathway) and PPAR (a metabolic signaling pathway).…”
Section: Bcr-abl1 Gatekeeper Mutationsmentioning
confidence: 99%
“…Clinical studies have established that ABCB1 expression levels are elevated in advanced stages of CML [42], and that high ABCB1 expression is associated with lower rates of MMR and imatinib resistance [43, 44]. At the molecular level, in vitro studies with the K562 cell line demonstrated that an increase in ABCB1-mediated drug efflux is a potential mechanism of resistance to imatinib [45, 46].…”
Section: Germline Genetic Determinants Of Drug Responsementioning
confidence: 99%
“…Nevertheless, researchers agree that expression levels of ABCB1 are strong predictors of imatinib responsiveness [43, 44] and could be monitored as early response markers in CML patients receiving imatinib [58]. …”
Section: Germline Genetic Determinants Of Drug Responsementioning
confidence: 99%